2020
DOI: 10.1111/jth.14977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral anticoagulants on hemostatic and thromboembolic complications in hip fracture: A systematic review and meta‐analysis

Abstract: Background: Hip fracture patients on oral anticoagulants (OACs) experience increased time-to-surgery and higher mortality compared to non-anticoagulated patients. However, it is unclear whether pre-injury OAC status and its associated operative delay are associated with worsening of peri-operative hemostasis or an increased risk of postoperative thromboembolism. Methods: We performed a systematic review to identify studies that directly compared hemostatic and thromboembolic outcomes among hip fracture patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Previous studies have reported that the use of VKA was associated with a delay in time-to-surgery and higher mortality for patients requiring emergency orthopaedic procedures [1459][1460][1461][1462] . Furthermore, these patients experience increased surgical blood loss and higher risk of red blood cell transfusions 1463 , highlighting the importance reversing the anticoagulation effect prior to emergency surgery.…”
Section: Daniel Caldeira Geno Merlimentioning
confidence: 99%
“…Previous studies have reported that the use of VKA was associated with a delay in time-to-surgery and higher mortality for patients requiring emergency orthopaedic procedures [1459][1460][1461][1462] . Furthermore, these patients experience increased surgical blood loss and higher risk of red blood cell transfusions 1463 , highlighting the importance reversing the anticoagulation effect prior to emergency surgery.…”
Section: Daniel Caldeira Geno Merlimentioning
confidence: 99%
“…It should be noted that the degree of surgical delay did not mitigate this bleeding risk, and there was no difference in the rate of postoperative thromboembolism, either. No subgroup effect was found based on anticoagulant type or degree of surgical delay [134].…”
Section: Oral Anticoagulantsmentioning
confidence: 78%
“…However, Leer-Salvensen reported a 5-fold increase in the rate of wound haematomas, though without complications [139]. Conversely, other studies such as the meta-analysis by Xu et al [134] and other cohort studies observed that DOACs were associated with a slightly increased risk of intra-operative bleeding and blood transfusion [141,142]. This association remained when including only patients operated on in less than 24 hours [142].…”
Section: Oral Anticoagulantsmentioning
confidence: 97%
See 2 more Smart Citations